Effects of Plasma Kallikrein Specific Inhibitor and Active-site Blocked Factor VIIa on the Pulmonary Vascular Injury Induced by Endotoxin in Rats - Uchiba, Mitsuhiro; Okajima, Kenji; Murakami, Kazunori; Okabe, Hiroaki; Okamoto, Shosuke; Okada, Yoshio (Thrombosis and Haemostasis, 1997)
The acute respiratory distress syndrome (ARDS) is a serious complication of sepsis. To evaluate the role of the coagulation system in the pathogenesis of ARDS in sepsis, we examined the effects of the administration of a synthetic plasma kallikrein specific inhibitor (PKSI) and of active-site blocked factor VIIa (DEGR-VIIa) on the pulmonary vascular injury induced by E. coli endotoxin (ET) in rats. Administration of PKSI prevented the pulmonary vascular injury induced by ET as well as pulmonary histological changes in animals administered ET, but it did not affect the intravascular coagulation. The opposite effect was seen with DEGR-VIIa, which prevented the intravascular coagulation but not the pulmonary vascular injury. PKSI did not inhibit the activation of the complement system induced by ET leading to the activation of neutrophils.Findings suggest that PKSI may prevent the pulmonary vascular injury induced by ET by inhibiting kallikrein, which activates the neutrophils. The intrinsic pathway of coagulation may be more important than the extrinsic pathway in the pulmonary vascular injury produced byET.